2014
DOI: 10.1186/1297-9716-45-10
|View full text |Cite
|
Sign up to set email alerts
|

Neospora caninum infection during early pregnancy in cattle: how the isolate influences infection dynamics, clinical outcome and peripheral and local immune responses

Abstract: This work studies the influence of Neospora caninum intra-species diversity on abortion outcome, infection dynamics in terms of parasite dissemination and peripheral-local immune responses in pregnant cattle. Animals were intravenously inoculated at day 70 of pregnancy with 107 tachyzoites of two isolates showing marked differences in virulence in vitro and in pregnant mouse models: Nc-Spain7, a high virulence isolate, and Nc-Spain8, a low-to-moderate virulence isolate. After inoculation, pregnancy was monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
103
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 46 publications
21
103
1
7
Order By: Relevance
“…Similar results have been reported in the placenta in naturally infected cattle (Rosbottom et al, 2011). The mixed pattern of up-regulation of cytokines in Neosporainfection has also been observed in several studies in experimental infections in both aborted and non-aborted dams at early pregnancy infections (Regidor-Cerrillo et al, 2014;Rosbottom et al, 2007Rosbottom et al, , 2008; at 110 days of gestation (Almería et al, 2003; or at 210 days of gestation (Bartley et al, 2013). Recently, Cantón et al (2014) observed a milder Th1 immune response based on infiltration of cytokine expressing cells in the placenta during later stages of gestation following Nc-1 infection that could partially explain the less severe clinical outcome when compared to early pregnancy.…”
Section: Gamma Interferon Versus Other Cytokinessupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have been reported in the placenta in naturally infected cattle (Rosbottom et al, 2011). The mixed pattern of up-regulation of cytokines in Neosporainfection has also been observed in several studies in experimental infections in both aborted and non-aborted dams at early pregnancy infections (Regidor-Cerrillo et al, 2014;Rosbottom et al, 2007Rosbottom et al, , 2008; at 110 days of gestation (Almería et al, 2003; or at 210 days of gestation (Bartley et al, 2013). Recently, Cantón et al (2014) observed a milder Th1 immune response based on infiltration of cytokine expressing cells in the placenta during later stages of gestation following Nc-1 infection that could partially explain the less severe clinical outcome when compared to early pregnancy.…”
Section: Gamma Interferon Versus Other Cytokinessupporting
confidence: 87%
“…There have been few studies comparing different isolates in vivo (Caspe et al, 2012;Chryssafidis et al, 2014;Regidor-Cerrillo et al, 2014) Regidor-Cerrillo et al (2014 compared two isolates, Nc-Spain7, a high virulence isolate, and NcSpain8, a low-to-moderate virulence isolate on heifers. Although all infected heifers suffered abortion when inoculated early in pregnancy, abortion occurred earlier in those inoculated with Nc-Spain7-infected animals with the parasite being more frequently detected in the placenta and fetuses.…”
Section: Strains Of Neospora Caninum and Abortionmentioning
confidence: 99%
“…In this model, which uses the N. caninum Spain7 (Nc-Spain7) isolate, which is highly virulent in vitro and in vivo in mice (21,22) as well as in sheep (23), all pups of infected dams died within 3 weeks; pups of noninfected dams survived. Thus, the model is reproducible, as shown in several recent studies (17,20,24).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to DCs, effector CD8+ T cell response is inhibited during H5N1 viral infection by IL-10 producing CD8+ Treg cells [75,76]. The induced manipulation toward the Th2 profile assures increased surviving possibility for different infective agents, such as viruses, chlamydias, and parasites [65, 67-69, 73,74,[77][78][79]. The early IL-10 production by T cell, B cell, and monocyte/macrophage (but not on NK and DC) activation can lead to chronicity of lymphocytic choriomeningitis and B hepatitis virus infections, and the IL-10-mediated early T cell Similarly to viral infections, parasite-induced IL-10 production by various immune cells is associated with impaired resistance to protozoan and nematodes [80,81,86,87].…”
Section: Principal Immune Conditionsmentioning
confidence: 99%